Asymmetric effects of spectator presence on home and away team performance: a natural experiment from the 2021 K League 1 season - Lee, Joonha; Park, Seoung-Jin; Suh, Dong Hun; Park, Hyung Jun (Frontiers in Psychology, 2025)
IntroductionThe presence of spectators is a well-known factor contributing to home advantage in competitive sports. However, isolating its direct effect on team performance has proven difficult. This study aims to assess the influence of spectator attendance on the performance of home and away teams using a natural experimental setting during the 2021 K League 1 season, which experienced regional differences in spectator policies due to the COVID-19 pandemic.MethodsThis retrospective observational study analyzed 162 matches in the 2021 K League 1 season. Match variables were categorized into three domains: outcome factors (e.g., points, win percentage), tactical factors (e.g., shots on target, total shots), and violation factors (e.g., fouls, cards) to evaluate team performance. Matches were classified according to the presence or absence of spectators and further stratified by whether they were home or away games. Group comparisons were performed using t-tests, one-way analysis of variance, and effect-size analysis (Cohen’s d).ResultsThe presence of spectators was associated with improved tactical performance in home matches, as evidenced by a greater number of shots on target (6.02 ± 3.08 vs. 4.40 ± 2.34, p = 0.041, d = 0.58) and total shots (11.46 ± 4.13 vs. 9.46 ± 3.48, d = 0.52). In contrast, spectator-related effects were more pronounced in away matches, particularly in outcome performance factors. Away teams with spectators had lower win percentage (0.22 ± 0.42 vs. 0.58 ± 0.52, d = 0.83), more goals conceded (1.58 ± 1.16 vs. 0.67 ± 0.89, p = 0.032, d = 0.82), and fewer points (0.96 ± 1.19 vs. 2.00 ± 1.28, d = 0.87) than those without spectators.ConclusionSpectator presence was associated with enhanced tactical performance by home teams. In contrast, its impact on away matches was more pronounced in outcome-related performance, suggesting that home crowds may exert psychological pressure that disrupts visiting teams’ execution and composure. These findings underscore the asymmetrical influence of spectatorship and enhance our understanding of home advantage in professional football.